English for business studies : a course for business studies and economics students : student's book - Mackenzie, Ian (Cambridge University Press, 1997)
The three sectors of the economy. Management. Company structure. Work and motivation. Management and cultural diversity. Recruitment. Labour relations. Production. Products.